PERNIKAHAN ADAT SUNDA PERSPEKTIF HUKUM ISLAM - Bunga Nurwiyatin Putri; Ruston Nawawi (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2021)
This article is the result of a qualitative field research. This article discusses a series of Sundanese traditional marriages from the perspective of Islamic law. The research location is in Caringin Village, Tegal Panjang Village, Sucinarja District, Garut Regency. This study concludes that the series of Sundanese traditional wedding ceremonies are not in conflict with fiqh law. The series consists of a) pre-marriage stage; b) stage of the marriage contract; and c) post-marriage contract stage. The three sets of Sundanese marriage traditions are in harmony with the law of fiqh. This argument is built by analyzing the three series with the jurisprudence of the four schools of thought, istihsan bi maqasid al-shariah, isthsan bi al'urf, and the text of the argument. Keywords: Sundanese traditional marria, Islamic law, urf, maqasid shari’ah DAFTAR PUSTAKA ‘Abidin, Ibnu. Roddul Mukhtar Ala Daril Mukhtar Syarah Tanwirul Absar Fiqhu Abu Hanabiyah, Muktabah Syamila. Abdillah, Imam Abi. 1994. Shahih Bukhari. Beirut : Dar Al-fikr. Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 Amin, H. A., Masrokhin, M., & Anwar, K. (2021). GUARDIANS CONCEPT IN QUR’AN PERSPECTIVE . SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam , 6(1), 95 - 114. https://doi.org/10.33752/sbjphi.v6i1.1642 Al-Asfihani, Al-Garib. Ttp. Mufradat al-Fash al-Qur’an. Dar al-Katibal-‘Arabi. Al-Asqalani, Ibnu Hajar. 2011. Bulughul Maram. Jakarta: Pustaka as-Sunnah. Al-Jaziri, Abdurrahman. 1986. Kitab ‘ala Mazahib Al-Arba’ah Juz IV. Dar ihya al-Turas al-Arabi. As-Shabuni, Muhammad Ali. 1972. Tafsir Ayat al-Ahkam min al-Qur’an. Kuwait: Dar al-Qur’an al-Karim. As-Syuti, Abdurrahman Jalaluddin. 1983. Al-Asybah wa an-Naza’ir fi Qawa’id wa Furu’ Fiqh asy Syafi’i. Beirut: Dar al-Kutub al-‘Ilmiyah. Az-Zuhaili, Wahbah. 1989. Al-Fiqh Al-Islam Wa Adilatuhu. Juz VII. Damsyiq : Dar Al-Fikr. Az-zukhaili, Wahbah. Ushul Fiqh al-Islami. Juz 2. Damaskus: Dar al-fikr Bowie, Fiona. 2000. The Anthropology of Religion. Oxford: Blackwell. Junus, Mahmud. 1989. Hukum Perkawinan Islam Menurut Madzhab: Sayfi’i, Hanafi, Maliki dan Hambali. Jakarta: Pustaka Mahmudiyah. Khalaf, Abdul Wahab. 1978. Ilmu Ushul al-Fiqh. Ttp. cet.12. Mustapa, Hasan. 2010. Adat Istiadat Sunda. c.3. Bandung: PT. Alumni. Pinolingga, Irna. 2015. Tradisi Mangakuinduak Sebagai Persyaratan Pernikahan Dalam Perspektif Hukum Islam, (Studi Kasus di kenagarian Muaro Takung Kecamatan Kamang Baru Kabupaten Sijunjung). Masters thesis, Institut Agama Islam Negeri Imam Bonjol Padang. Yunus, Mahmud. 1979. Hukum Pernikahan dalam Islam. Jakarta: Hidakarya Agung. Zahra, Muhammad Abu. 1957. Al-Ahwal al-Syahsiyah. Qahirah: Dar al-Fikr al-‘Arabi.